RELASI AGAMA DAN NEGARA UNTUK PEMBANGUNAN INDONESIA DALAM KONTEK GOOD GOVERNANCE - Wisri Wisri; Mohammad Asra (LP2M Universitas Ibrahimy, 2015)
The concept of government with the authority of God is not in direct contrast to the concept of theocracy whose character is essentially the direct rule of God. God is God, and man is His servant. But one thing to keep in mind that God does not regulate directly, preferably, the power of God delegated to His Messenger, Muhammad duty to spread the new religion and sharia, which all comes from God. Therefore, the Islamic system of government with the law of God as the primary source of authority, can not be categorized as a form of theocratic government directly under the administration.In simple terms the State is the organization in the region that has the highest legal authority and obeyed by his people. Pancasila as the basic philosophy of the state, the state ideology. Pancasila is used as the basis for regulating the conduct of the state. Therefore, efforts to achieve good governance (good governance) is a good faith which has always been a political agenda in every leadership. Indonesia periodization is one country that is rather difficult to be separated from the cultural practices of corruption that has taken hold in the recesses of government. Even today has a resistance to fight against corruption and fighting corruption. A special team has been formed, but corruption is unstoppable with all the tricks. Therefore, routine effort required in order to create good governance and governance fun